Optimized QR Code-Based Authentication System for Attendance Management - Abirami K, Rama; Rohann, Santhana (Acta Pedagogia Asiana, 2026)
In the modern technological era, various innovations have been developed to simplify and automate tasks that were previously difficult or time-consuming. Institutions such as gymnasiums, universities, and corporate offices have widely adopted automated systems to manage memberships, maintain student records, and monitor employee working hours. As automation became increasingly integrated into everyday operations, attendance monitoring systems in educational institutions also evolved significantly. In the past, attendance was typically recorded manually using paper-based methods. However, recent technological advancements have introduced alternative solutions such as biometric systems, Radio Frequency Identification (RFID), barcodes, and Quick Response (QR) codes to track attendance in large academic institutions. Despite these technological developments, several challenges remained in ensuring that attendance records were accurate, secure, and fair. Some systems involved high implementation costs, while others were vulnerable to misuse, such as students sharing attendance cards or forwarding attendance links to peers. These limitations reduced the reliability of attendance monitoring systems. Therefore, this study proposed an optimized QR code-based authentication system designed to improve the accuracy and reliability of attendance monitoring in academic institutions. The proposed approach aimed to enhance authentication mechanisms, thereby reducing fraudulent attendance practices and improving the efficiency of attendance management.